2002
DOI: 10.1093/tropej/48.6.380
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Muscle Weakness--An Unusual Presentation of Celiac Disease

Abstract: The identification of the etiology of metabolic bone disease that leads to myopathy is important as this type of muscle weakness often responds fully to treatment. We present the case history of an 11-year-old girl with celiac disease who had rickets masquerading as muscle weakness and bone pains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Vitamin D deficiency cannot be excluded as a contributing factor for the myopathy in this case, because the patient had an elevated serum alkaline phosphatase, a sensitive marker consistent with osteomalacia, despite normal serum calcium and phosphate levels. Cases of myopathy and vitamin D deficiency in celiac disease have been reported 3, 23, 44. However, besides proximal weakness, all of these patients had prominent bone pain, which was not present in our patient.…”
Section: Discussioncontrasting
confidence: 45%
“…Vitamin D deficiency cannot be excluded as a contributing factor for the myopathy in this case, because the patient had an elevated serum alkaline phosphatase, a sensitive marker consistent with osteomalacia, despite normal serum calcium and phosphate levels. Cases of myopathy and vitamin D deficiency in celiac disease have been reported 3, 23, 44. However, besides proximal weakness, all of these patients had prominent bone pain, which was not present in our patient.…”
Section: Discussioncontrasting
confidence: 45%
“…In children, muscle involvement due to vitamin D deficiency was reported in a 5-year-old child with cholestatic liver disease(1) and in another 11-yearold girl with celiac disease (2). In our case, vitamin D deficiency was associated with phenytoin therapy.…”
Section: From the Department Of Pediatrics University College Of Medmentioning
confidence: 51%
“…VOLUME 47 __ JULY 17, 2010 I n children, muscle weakness due to vitamin D deficiency is rarely reported (1,2). We herein report one such case.…”
mentioning
confidence: 82%
“…Rickets-associated myopathy was reported as the only presenting complaint of celiac disease even in a 5-year-old girl [12]. Jain et al [13] reported an 11-year-old girl who had bone pain, waddling gait, Gowers' sign, and supracondylar fracture of humerus. Anemia, short stature, and associated rickets were the other signs suggestive of a malabsorptive state.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the typical skeletal alterations for adult osteomalacic patients were not detected. Bone and joint pain, especially at the shoulder, rib cage, pelvic girdle, and lower back, could be observed in patients with osteomalacia [5,8,10,11,13,23,24]. Pain at hip and shoulders as well as diffuse rib cage tenderness are most useful criteria for distinguishing osteomalacia from osteoporosis [25].…”
Section: Discussionmentioning
confidence: 99%